Seasonal characteristics of phytoplankton bloom phenology in the northern Benguela Upwelling System - Matlakala, Mmakabele Lebogang (Department of Biological Sciences, 2020)
Seasonal phytoplankton blooms in the Benguela Upwelling System (BUS) play a crucial role in ecosystem services and driving climate change through air-sea gas exchanges. Upwelling systems are particularly are sensitive to effects of climate change including the transport of nutrients, which influence the composition of phytoplankton communities. This is important because species composition affects a number of key processes that have significant climate feedbacks. This study uses historical long-term in situ data (at 10 and 70 NM stations) as well as OC-CCI satellite ocean colour data to investigate seasonal phytoplankton bloom phenology and community structure of diatoms, dinoflagellates and coccolithophores in the northern BUS. The seasonal cycle of satellite chlorophyll was used to determine the timing of bloom initiation at inshore and offshore boxes that overlapped the in situ stations. An ocean colour algorithm to detect coccolithophore presence and absence was used to determine the inshore-offshore seasonal cycle of coccolithophores. Results indicate a gradual decrease in chlorophyll concentration further offshore as well as high intra-seasonal, inter-annual and spatial variability. Offshore blooms initiate later and last longer than inshore blooms which have a higher magnitude. Diatoms are dominant over dinoflagellates and coccolithophores throughout the northern BUS, with higher concentrations observed at the inshore station (10 NM) for all three phytoplankton groups. However, satellite results show a higher presence of coccolithophores in the offshore region during spring and summer that is associated with periods of strong stratification. This study provides a better understanding of the characteristics of the phytoplankton seasonal cycle in the northern BUS which is useful for detecting trends and possible change associated with climate change forcing in response to global warming.